OPPRESSION TO EMPOWERMENT: SYRIAN REFUGEE WOMEN IN WARGA’S OTHER WORDS FOR HOME - Yuliati, Retno (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2021)
This study offers an in-depth reading of Jasmine Warga’s Other Word for Home. Deploying descriptive analytical method and P.H. Collins’ concepts of Matrix of Domination and Self-Definition, this study aims to analyze the themes of women’s oppression and women’s empowerment in this book. Findings suggest that Jude and her mother, Syrian refugee women, are oppressed both in Syria and in the US due to their overlapping identity markers (gender, class, ethnicity, religion) in four domains of power (structural, disciplinary, hegemonic, interpersonal). In Syria, they are oppressed in structural domain by Syrian government. Meanwhile in the US, they are oppressed in disciplinary domain to preserve her subordination. Both Jude and Mama are also oppressed by the negative hegemonic ideologies that evolving around Syrian refugees, Muslim, and Arab women. At last, they are oppressed in interpersonal level in everyday life. However, by nurturing certain behaviors in Self-Definition (self-valuation, self-reliance, personal empowerment), they help fostering their empowerment to resist the intersecting oppressions. Penelitian ini menyajikan pembacaan komprehensif terhadap buku Other Words for Home karya Jasmine Warga. Menggunakan metode deskriptif-analitis dan konsep Matriks Dominasi dan Definisi-Diri P.H. Collins, penelitian ini bermaksud untuk menganalisis tema penindasan terhadap perempuan dan pemberdayaan perempuan dalam buku ini. Ditemukan bahwa Jude dan ibunya tertindas baik di Suriah dan Amerika Serikat karna beragam penanda identitas menyilang mereka (jenis kelamin, kelas, etnisitas, agama) dalam empat wilayah kekuasaan (struktural, disipliner, hegemonik, antar individu). Di Suriah, Jude dan ibunya tertindas dalam wilayah struktural oleh pemerintah Suriah. Sementara di Amerika, mereka tertindas dalam wilayah disipliner agar mereka tetap menjadi seorang bawahan. Jude dan ibunya juga tertindas oleh ideologi hegemonik negatif mengenai pengungsi Suriah, Muslim, dan perempuan Arab. Terakhir, mereka juga tertindas dalam wilayah antar individu dalam kehidupan sehari-hari. Meski begitu, sikap-sikap dalam Definisi-Diri (penghargaan diri, kemandirian, pemberdayaan pribadi) mendukung pemberdayaan mereka dalam melawan penindasan menyilang.